(untitled) (Bangladesh Journal of Botany, 2021)
Effects of different dosages of potassium silicate fertilizer on photosynthetic characteristics and yield of winter wheat under field conditions were studied. Four different dosages: 0, 45, 90 and 135kg/ha were applied. Results showed that the chlorophyll content, net photosynthetic rate of wheat flag leaf firstly increased and then decreased with the increase of levels of potassium silicate fertilizer. By the change of SPAD values after flowering, when the application of potassium silicate fertilizer was 90 kg/ha, the existence time of chlorophyll in flag leaf was significantly long, and the net photosynthetic rate was significantly increased. The 1000-grain weight of winter wheat significantly increased and the yield the highest. Overall, when the applied amount of potassium silicate fertilizer was 90 kg/ha, the performances of winter wheat were best. Bangladesh J. Bot. 50(4): 1127-1132, 2021 (December)